Functionalized microfibers for field-responsive materials and biological applications. (September 2015) - Bossis, Georges; Marins, Jéssica A; Kuzhir, Pavel; Volkova, Olga; Zubarev, Andrey
Fiber-like particles are mostly used as basic components of electrorheological and magnetorheological suspensions because of their lower sedimentation rate and higher yield stress. The theoretical approach of the yield stress mainly rests on the interaction between two spherical particles. We analyze the interactions between fibers, taking into account the contribution of friction between fibers. Comparing experimental results to the model we conclude that it is not possible to clearly assess what is the part due to the friction in the increase of the yield stress which, on the other hand, can be explained by the increase of magnetization of the particles due to their lower demagnetization factor. We also show in an experiment between two nickel fibers that the rupture force between the fibers is very sensitive to the shape of their extremity. Besides the particles made of the same material, the core-shell particles made of different materials can also present advantages. We compare electrorheological suspensions made of pure polyaniline to those made of sepiolite and coated with polyaniline. We show that the much higher yield stress obtained with the hybrid particles is essentially due to a higher aspect ratio of sepiolite fibers.